ChemInform Abstract: Pd‐Mediated Multicomponent Synthesis of Highly Functionalized Pyridines and Consequential C—C Coupling Using Suzuki Reaction in One Pot: Their in vitro Evaluation as Potential Antibacterial Agents. Issue 9 (March 2015) - Srinivasula Reddy, L.; Ram Reddy, T.; Gangi Reddy, N. C.; Mohan, Reddy Bodireddy; Lingappa, Y.
Abstract Some of the new compounds, (Vb), (Vg), (Vh), show good inhibition against the multi drug resistant gram‐negative bacterial strain Klebsiella pneumoniae (MTCC 109), nearly equivalent to that of reference drug chloramphenicol.